Bone Marrow Mesenchymal Stem Cells-Derived Exosomes Inhibit Apoptosis of Pulmonary Microvascular Endothelial Cells in COPD Mice Through miR-30b/Wnt5a Pathway - Song Q; Zhou A; Cheng W; Zhao Y; Liu C; Zeng Y; Lin L; Zhou Z; Peng Y; Chen P (International Journal of Nanomedicine)
Qing Song,1– 4 Aiyuan Zhou,5 Wei Cheng,1– 4 Yiyang Zhao,6 Cong Liu,1– 4 Yuqin Zeng,1– 4 Ling Lin,1– 4 Zijing Zhou,1– 4 Yating Peng,1– 4 Ping Chen1– 4 1Department of Respiratory and Critical Care Medicine, the Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of China; 2Clinical Medical Research Center for Pulmonary and Critical Care Medicine in Hunan Province, Changsha, 410011, People’s Republic of China; 3Diagnosis and Treatment Center of Respiratory Disease, Central South University, Changsha, Hunan, 410011, People’s Republic of China; 4Research Unit of Respiratory Disease, Central South University, Changsha, Hunan, 410011, People’s Republic of China; 5Department of Respiratory and Critical Care Medicine, the Xiangya Hospital of Central South University, Changsha, Hunan, 410011, People’s Republic of China; 6Ultrasound Imaging Department, Xiangya Hospital of Central South University, Changsha, Hunan, 410083, People’s Republic of ChinaCorrespondence: Ping Chen, Department of Respiratory and Critical Care Medicine, the Second Xiangya Hospital, Central South University, Renmin Middle Road, Changsha, Hunan, 410011, People’s Republic of China, Tel 13873115563, Email pingchen0731@csu.edu.cnBackground: Bone marrow mesenchymal stem cells (BMSCs)-derived exosomes are rich in a variety of active substances, including microRNA (miR) and have shown powerful therapeutic effects to ameliorate cell injury and diseases. However, the role of BMSCs-derived exosomes on chronic obstructive pulmonary disease (COPD) has been poorly studied. In addition, pulmonary microvascular endothelial cells (PMVECs) apoptosis contributes to the onset of COPD. Inhibition of PMVECs apoptosis can reverse COPD changes. Therefore, the aim of this study was to explore the role of BMSCs-derived exosomes in the apoptosis of PMVECs in COPD and to investigate the potential mechanisms.Methods: We isolated and characterized normal mouse BMSCs-derived exosomes and PMVECs. We performed miR sequencing of BMSCs-derived exosomes. We transfected PMVECs with the miR-30b mimic and Wnt5a overexpression plasmid to assess the underlying mechanisms. Cigarette smoke extract (CSE)-induced COPD mice were treated with exosomes and HBLV-mmu-miR-30b via intratracheal instillation. Finally, we determined the expression of miR-30b and Wnt5a in tissues from patients with COPD.Results: BMSCs-derived exosomes could significantly reduce apoptosis of CSE-induced PMVECs and increase the expression of miR-30b (p< 0.05). Based on miR sequencing, miR-30b was highly enriched in BMSCs-derived exosomes. The knockdown of miR-30b in BMSCs-derived exosomes could increase the apoptosis of CSE-induced PMVECs (p< 0.05). miR-30b overexpression significantly reduced apoptosis and repressed Wnt5a protein expression in CSE-induced PMVECs (p< 0.05). Furthermore, Wnt5a overexpression reversed the anti-apoptotic effect of miR-30b on CSE-induced PMVECs (p< 0.05). In addition, compared with the COPD group, treatment with BMSCs-derived exosomes and miR-30b overexpression could alleviate emphysema changes, decrease the mean linear intercept and alveolar destructive index, reduce apoptosis, increase the expression of miR-30b, and decrease the expression of Wnt5a in lung tissue (p< 0.05). Finally, miR-30b expression was decreased in patients with COPD, while Wnt5a expression was increased in these patients (p< 0.05).Conclusion: BMSCs-derived exosomes could improve the damage of COPD perhaps by delivering miR-30b. miR-30b could reduce apoptosis of CSE-induced PMVECs by targeting Wnt5a. Keywords: chronic obstructive pulmonary disease, bone marrow mesenchymal stem cells, exosomes, miR-30b, Wnt5a